The Requirement of Father’s Permission in the Marriage of an Adult Virgin: A Jurisprudential Study in the Imami and Hanafi Schools of Thought - Jassim Nasser , Assist. Prof. Abbas (Basra studies journal, 2026)
The research examines the requirement of a father’s consent in the marriage of a mature virgin woman according to Imami and Hanafi jurisprudence. It begins by defining the concept of “condition” linguistically and technically as understood by scholars of both the Imami and Hanafi schools. The study then addresses the juristic disagreement within Imami jurisprudence regarding the requirement of the father’s consent. Scholars unanimously agree on requiring consent in the case of a minor or an immature woman. They also agree that it is not required in the marriage of a mature previously married woman (divorced or widowed). However, the marriage of a mature virgin woman remains a point of disagreement, with opinions ranging between requiring consent, not requiring it, or requiring joint consent. Each view is supported by different narrations and Qur’anic verses that emphasize the woman’s consent and free choice. Many Imami jurists tend toward precaution by combining the woman’s consent with that of her guardian. In contrast, Hanafi jurisprudence permits a mature virgin woman to contract her own marriage without her father’s consent under certain conditions, although it is recommended that she seek her guardian’s permission.